The mechanosensitive Piezo1 channels contribute to the arterial medial calcification - Szabó, László; Balogh, Norbert; Tóth, Andrea; Angyal, Ágnes; Gönczi, Mónika; Csiki, Dávid Máté; Tóth, Csaba; Balatoni, Ildikó; Jeney, Viktória; Csernoch, László; Dienes, Beatrix (Frontiers in Physiology, 2022)
Vascular calcification (VC) is associated with a number of cardiovascular diseases, as well as chronic kidney disease. The role of smooth muscle cells (SMC) has already been widely explored in VC, as has the role of intracellular Ca2+ in regulating SMC function. Increased intracellular calcium concentration ([Ca2+]i) in vascular SMC has been proposed to stimulate VC. However, the contribution of the non-selective Piezo1 mechanosensitive cation channels to the elevation of [Ca2+]i, and consequently to the process of VC has never been examined. In this work the essential contribution of Piezo1 channels to arterial medial calcification is demonstrated. The presence of Piezo1 was proved on human aortic smooth muscle samples using immunohistochemistry. Quantitative PCR and Western blot analysis confirmed the expression of the channel on the human aortic smooth muscle cell line (HAoSMC). Functional measurements were done on HAoSMC under control and calcifying condition. Calcification was induced by supplementing the growth medium with inorganic phosphate (1.5 mmol/L, pH 7.4) and calcium (CaCl2, 0.6 mmol/L) for 7 days. Measurement of [Ca2+]i using fluorescent Fura-2 dye upon stimulation of Piezo1 channels (either by hypoosmolarity, or Yoda1) demonstrated significantly higher calcium transients in calcified as compared to control HAoSMCs. The expression of mechanosensitive Piezo1 channel is augmented in calcified arterial SMCs leading to a higher calcium influx upon stimulation. Activation of the channel by Yoda1 (10 μmol/L) enhanced calcification of HAoSMCs, while Dooku1, which antagonizes the effect of Yoda1, reduced this amplification. Application of Dooku1 alone inhibited the calcification. Knockdown of Piezo1 by siRNA suppressed the calcification evoked by Yoda1 under calcifying conditions. Our results demonstrate the pivotal role of the Piezo1 channels in arterial medial calcification.